Genetic Types of the tp12cx Strike-Slip Fault Segments and Their Role in Controlling Reservoirs in the Tarim Basin - Lv, Yanping; Ma, Hailong; Wang, Zhen; Deng, Guangxiao; Wen, Huan (Frontiers in Earth Science, 2022)
The change of motion mode of multistage active strike-slip faults controls the segmentary types of strike-slip faults, which is seldom studied.Based on high-precision 3D seismic data and the principle of structural analysis, this paper defines the structural evolution characteristics of the tp12cx strike-slip fault in the key structural period and identifies the fault segmentation types. Combined with the statistical results of drilling production data and fault width, and fault width, it is demonstrated that different fault segments display various reservoir architecture and hydrocarbon potential. The tp12cx strike-slip fault experienced two phases of tectonic activity controlling reservoir development: the middle Caledonian and the late Caledonian to early Hercynian. During the middle Caledonian period, a left-lateral and left-step strike-slip fault was formed. The overlapping segments of the left steps were transtension zones, and the rest were pure strike-slip segments. From the late Caledonian to the early Hercynian, the movement mode changed from left-lateral to right-lateral, and the arrangement of left steps remained unchanged, forming right-lateral and left-step strike-slip faults. That is, as a weak zone, the transtension zones of all the preexisting overlapping segments took the lead in moving into many pure strike-slip segments and maintained the transtensional property. During the right-lateral slipping process of all the original pure strike-slip segments along the fault, they were blocked and squeezed by the surrounding rocks on both sides, forming a series of “positive” flower-shaped fault anticlines, which became overlapping segments, and the fault property became transpressional. Under the continuous action of the right-lateral slipping, a regional right-lateral and right-step strike slip fault formed. The interiors of the right-step-arranged faults were composed of the left-step arranged faults. Among them, the right-step overlapping segments were weakly step overlapping segments were weakly transtensional, and the larger the fault width of the internal left step pure strike slip and overlapping segments, the stronger the dissolution. The deformation of the right-step pure strike-slip segments was weak and basically maintained the characteristics of the previous stage. According to the evolution and superposition of pure strike-slipped and overlapped segments and the changes in fault properties, four types of strike-slip fault segments and corresponding reservoir models are divided. Type I: left-step pure strike-slip segment + left-step transpressional segment + right-step transtensional segment; Type II: left-step transtensional segment + left-step pure strike-slip segment + right-step transtensional segment; Type III: left-step pure strike-slip segment + left-step transpressional segment; and Type IV: left-step transtensional segment + left-step pure strike-slip segment. The fault width and oil production of type II and type IV with transtensional properties are much larger than those of type I and type III with transpressional properties.